Airborne radio echo sounding of glaciers in Svalbard - Drewry, D. J.; Liestøl, O.; Neal, C. S.; Orheim, O.; Wold, B. (Polar Record, 1980)
During April–May 1980 the Scott Polar Research Institute (SPRI) and Norsk Polarinstitutt (NPI) conducted a joint programme of radio echo sounding (RES) in Svalbard. The principal aims were to evaluate the performance of SPRI 60 MHz echo sounding equipment of Svalbard glaciers, to measure ice thickness over a wide range of conditions, and to investigate specific glaciers which are the focus of current glaciological studies.